INTEGRATED ACADEMIC SERVICE INFORMATION SYSTEM (SIPAKATAU): STUDY OF EDUCATION SERVICE POLICY AT IAIN PALOPO - Dodi Ilham Mustaring; Muhammad Yaumi; Saprin Saprin (Universitas Dharma Wacana, 2022)
This study aims to 1) determine the service quality of the integrated academic service information system (SIPAKATAU) at IAIN Palopo. 2) Describe the implementation of the education service policy of IAIN Palopo. This research uses mixed methods, with an approach to academic and managerial information system research using explanatory sequential design. Data collection techniques are observation, interviews, questionnaires, and documentation. Data analysis consists of data reduction, condensation, presentation, and conclusion drawing.The results showed that: 1) The service quality of the SIPAKATAU was categorized as good by looking at the results of descriptive statistical tests on lecturer responses with an average value of 0.57 and a standard deviation of 0.502, students with an average score of 0.62 and a standard deviation of 0.493 and education staff with an average value of 0.69 and a standard deviation of 0.467 because more than half the number of respondents who chose to agree with the SIPAKATAU. 2) Education policy services at IAIN Palopo through the SIPAKATAU application service greatly facilitate users in all academic aspects, both administratively and in the teaching and learning process, which is currently in the online learning category. In this case, service users are helped by an integrated academic service information system service because the teaching and learning process can occur when students are in their respective areas. Therefore, SIPAKATAU is very useful. It helps users provide services because some of the services can already be done in the SIPAKATAU application so that academic services at IAIN Palopo are better and on target when learning demands increasingly sophisticated technology and technological developments are also increasingly modern. IAIN Palopo's policy challenges implementing educational services, such as the uneven access to the information contained in the SIPAKATAU service to service users in the era of the industrial revolution 4.0.Research Implications: 1) IAIN Palopo's educational services should be evaluated every semester by evaluating the performance between students, lecturers, and education staff. 2) Education policy services at IAIN Palopo require developing the SIPAKATA application to refine further the features contained in the application to support the quality of education in the face of the industrial revolution era with increasingly sophisticated educational technology. 3) The SIPAKATAU still requires socialization on services. 4) SIPAKATAU has a vision and mission at the beginning of the manufacturing process so that it is carried out in its development to achieve the goals in its use according to the needs of service users.